Community built environment attributes moderate the relationship between family support and depression among older adults in urban China - Qian Sun; Yingqi Guo; Yanlong Yin; Youwei Wang; Nan Lu (BMC Geriatrics)
Abstract Background This study examined the moderating effects of built environment attributes on the relationship between family support and depressive symptoms among community-dwelling older adults in urban China. Methods Quota sampling was used to recruit participants from Tianjin (one of the four municipalities in China) and Shijiazhuang (the capital city of Hebei Province). Face-to-face interviews were conducted with 799 respondents aged 60 years and older, in either their homes or local community centers. Multi-level modeling was used to test the proposed model. Results This study found that family support was negatively associated with depressive symptoms. Green spaces were negatively associated with depressive symptoms among older participants, although most indicators of the objective built environment attributes were not. The moderation analysis revealed a significant interaction effect between family support and green spaces on depressive symptoms. Specifically, living in areas with a higher percentage of green spaces may mitigate the negative effects of lower levels of family support on depression. Conclusions This study contributes a new direction for investigating the relationship between family support and depressive symptoms among community-dwelling older adults in China by considering the moderating effect of objective built environment attributes. The findings may guide practices and urban design in mental health promotion for older adults. Specifically, this study provides evidence useful for both policy designers and urban planners by highlighting modifiable environmental and objective factors that can promote community mental health for older adults who find it difficult to obtain family support in modern society.